Swallow Imagery in the Spring Fresco - Chloe Lovelace (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
The Spring Fresco, or the fresco of the Room of the Lilies, from the Delta Complex at the Late Bronze Age site of Akrotiri is considered to be the first painting of a nature scene in European art history. With this has come significant analysis of the fresco, which covers three walls of the small room. There has been much discussion regarding the room’s purpose and the iconographic meaning of the images in the fresco, especially in regards to the flying swallows. Initially thought to be birds in courtship, the birds are now thought to be engaging in behavior that is much more substantive. Present scholarly opinion is divided about whether they display parental or combative behavior. However, neither of these explanations fully accounts for all the bird behavior depicted in this room or for the birds’ relationship to the other components of the painting: the lilies and the multi-colored rocks. Moreover, neither interpretation accords well with the purported cultic function of the room. This paper seeks to offer an alternative explanation of the swallows and the lilies as representations of the cycle of life. This interpretation accounts for all of the swallow and lily images in the room and it fits its cultic context much better, thus providing a deeper and more holistic understanding of the entire assemblage.